2015
DOI: 10.3390/w7073396
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Urban Pluvial Flood Hazard Maps Based upon a Spatial-Temporal Rainfall Generator

Abstract: It is a common practice to assign the return period of a given storm event to the urban pluvial flood event that such storm generates. However, this approach may be inappropriate as rainfall events with the same return period can produce different urban pluvial flooding events, i.e., with different associated flood extent, water levels and return periods. This depends on the characteristics of the rainfall events, such as spatial variability, and on other characteristics of the sewer system and the catchment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…Strongest correlations were found with the variables d 0.25 and d 1 . This confirms the relevance of sub-daily temporal resolutions when investigating the impact of rainfall on urban hydrology (Blenkinsop et al, 2017;Ochoa-Rodriguez et al, 2015;Romero et al, 2011;Simões et al, 2015). It should be noted that relations found are strongly dependent on the spatial aggregation scale.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Strongest correlations were found with the variables d 0.25 and d 1 . This confirms the relevance of sub-daily temporal resolutions when investigating the impact of rainfall on urban hydrology (Blenkinsop et al, 2017;Ochoa-Rodriguez et al, 2015;Romero et al, 2011;Simões et al, 2015). It should be noted that relations found are strongly dependent on the spatial aggregation scale.…”
Section: Discussionsupporting
confidence: 67%
“…Research has shown that these variable resolutions 5 influence hydrodynamic model outputs (Ochoa-Rodriguez et al, 2015). A variable spatial resolution of rainfall also appears to be a significant parameter in the determination of flood probabilities (Simões et al, 2015). Recently, an alternative framework is proposed, in which the variable of interest is the time needed to accumulate a fixed amount of rainfall or flow instead of a variable amount over a fixed arbitrary time (Ten Veldhuis and Schleiss, 2017).…”
Section: Approaches To Quantifying Urban Pluvial Flooding Occurrence mentioning
confidence: 99%
See 2 more Smart Citations
“…Its aim is to decompose original series into small number of independent and interpretable components like oscillatory components, a structureless noise, and a slowly varying trend. Moreover, [4] also illustrate that SSA technique performs four steps. First, computing the trajectory matrix.…”
Section: Introductionmentioning
confidence: 95%